ANALISIS STRATEGI KOMUNIKASI WORD OF MOUTH PADA UMKM LELA DUSUN NGROTO DESA SUMOGAWE - Tika Nurul Annisa; Dewi Kartika Sari; Antonius Suparno (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
The rapid development of information technology has changed the traditional and conventional marketing communication methods to digital-based. Word of mouth communication has also begun to evolve into electronic word of mouth. Although currently electronic word of mouth is preferred as a marketing communication tool in business, there are still some UMKM that rely on marketing communication through traditional word of mouth. So the purpose of this study is to determine the word of mouth communication strategy in LELA UMKM in Ngroto Sumogawe Hamlet that can survive and grow in the current digital era. This study uses the word of mouth theory using elements or indicators according to Sernovitz and Barry J. Babin. The research method used is descriptive qualitative with a qualitative explanatory type. The results of the study show that the word of mouth communication strategy in LELA UMKM in Ngroto Sumogawe Hamlet uses traditional word of mouth. The results of the word of mouth analysis using elements or indicators according to Sernovitz and Barry J. Babin, show that the success of word of mouth in LELA UMKM does not always depend on the elements or indicators that have been described. The success of word of mouth in LELA UMKM depends on the quality of its products and services.